2005
DOI: 10.1200/jco.2005.05.098
|View full text |Cite
|
Sign up to set email alerts
|

Randomized Phase III Trial of Capecitabine Compared With Bevacizumab Plus Capecitabine in Patients With Previously Treated Metastatic Breast Cancer

Abstract: Bevacizumab was well tolerated in this heavily pretreated patient population. Although the addition of bevacizumab to capecitabine produced a significant increase in response rates, this did not translate into improved PFS or overall survival.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

24
656
5
17

Year Published

2006
2006
2011
2011

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 1,237 publications
(702 citation statements)
references
References 24 publications
24
656
5
17
Order By: Relevance
“…Similar findings were observed when bevacizumab (7.5 or 15 mg kg -1 every 3 weeks) was combined with docetaxel (100 mg m -2 every 3 weeks), although the treatment effect for bevacizumab was not as pronounced [77]. Bevacizumab did not prolong PFS when used as the second or greater-line therapy in combination with capecitabine, although it did significantly improve the response rate (20 vs. 9%, P = 0.01) [78]. Adjuvant trials are now in progress to evaluate the role of bevacizumab in combination with chemotherapy.…”
Section: Adjuvant Biological Therapysupporting
confidence: 64%
“…Similar findings were observed when bevacizumab (7.5 or 15 mg kg -1 every 3 weeks) was combined with docetaxel (100 mg m -2 every 3 weeks), although the treatment effect for bevacizumab was not as pronounced [77]. Bevacizumab did not prolong PFS when used as the second or greater-line therapy in combination with capecitabine, although it did significantly improve the response rate (20 vs. 9%, P = 0.01) [78]. Adjuvant trials are now in progress to evaluate the role of bevacizumab in combination with chemotherapy.…”
Section: Adjuvant Biological Therapysupporting
confidence: 64%
“…Grade 2 diarrhea occurred in only 5% of patients compared with 16% of patients who received conventional dosing. 12 There were no reports of grade 3/4 diarrhea or grade !2 nausea or vomiting. These findings support optimization of the therapeutic index, because diarrhea can be a significant and potentially life-threatening adverse event.…”
Section: Discussionmentioning
confidence: 99%
“…In pilot experiments, we have shown that trastuzumab and the PI3K inhibitor LY294002 have an additive effect on BT474 cell growth in cell culture (data not shown). Combination therapy with trastuzumab and a therapeutic molecule targeting VEGF and/or its receptors, such as the recombinant humanized monoclonal anti-VEGF antibody bevacizumab (Pegram and Reese, 2002;Miller et al, 2005) and VEGF-TRAP (Holash et al, 2002), may prove active against HER2-overexpressing breast cancers.…”
Section: Discussionmentioning
confidence: 99%